2006
DOI: 10.1097/01.ccm.0000194539.50905.81
|View full text |Cite
|
Sign up to set email alerts
|

Current issues in critical care of the human immunodeficiency virus-infected patient*

Abstract: HIV-infected patients are less likely to be admitted to the intensive care unit with opportunistic infections but more likely to be admitted with problems unrelated to HIV infection or with conditions related to antiretroviral therapy. With current management strategies, more patients survive intensive care unit admission. Intensivists need to be familiar with antiretroviral therapy to recognize life-threatening toxicities unique to these drugs; to avoid drug interactions, which are extremely common and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 62 publications
3
32
0
Order By: Relevance
“…24 A decision needs to be taken whether the ARVs should be stopped, continued or whether to switch to another regimen. 27 The exact risk of stopping HAART in the ICU patient is largely unknown, but carries the risk of viral load rebound and drug resistance. The SMART study, testing intermittent ARV treatment guided by CD4 count, clearly demonstrated increased rates of opportunistic disease and death.…”
Section: Alternative Routes For Haart Administrationmentioning
confidence: 99%
See 4 more Smart Citations
“…24 A decision needs to be taken whether the ARVs should be stopped, continued or whether to switch to another regimen. 27 The exact risk of stopping HAART in the ICU patient is largely unknown, but carries the risk of viral load rebound and drug resistance. The SMART study, testing intermittent ARV treatment guided by CD4 count, clearly demonstrated increased rates of opportunistic disease and death.…”
Section: Alternative Routes For Haart Administrationmentioning
confidence: 99%
“…39 The intensivist needs to be familiar with ARV therapy and its possible toxicity. 27 Life-threatening toxicities are discussed above, and include lactic acidosis, hypersensitivity syndromes, druginduced hepatitis, IRIS and cardiovascular events. 27 The associated drug interactions (see Table II) and metabolic complications, as stated previously, cause major management difficulties in the ICU.…”
Section: Alternative Routes For Haart Administrationmentioning
confidence: 99%
See 3 more Smart Citations